Fabrication of PbSe colloidal quantum dot solar cells using low-temperature Li-doped ZnO electron transport layer. (15th May 2023) - Bashir, Rabia; Kashif Bilal, Muhammad; Bashir, Amna; Ali, Awais
Highlights: Introduction of low-temperature undoped and 1–3 wt% lithium (Li) doped sol–gel-derived ZnO (LZO) and utilized them as ETLs in PbSe QDSCs. The solution of the Li-doped ZnO was obtained by the addition of LiCl into ZnO sol–gel with a Li/Zn molar ratio of 1%, 2%, and 3%. LZO-based QDSCs exhibit the highest PCE of 10.80% with an FF of 69.50%, open-circuit voltage ( Voc ) of 0.62 V, and current density ( Jsc ) of 27.67 mAcm −2 when doped with 2%. The photoelectric properties ( Voc, Jsc, FF, and PCE) were almost unchanged after 40 days. Abstract: The lead selenide quantum dots (PbSe QDs) have incredible features because of their tunable bandgap and synthesis process at low temperatures. Aside from the highly effective QDs active layer, the electron transport layer (ETL) also plays a significant part in obtaining high-efficiency colloidal quantum dots solar cells (CQDSCs). Here, we introduce undoped and 1–3% lithium-doped zinc oxide (LZO) sol–gel as an ETL and utilized it in CQDSCs to achieve high efficiency. ZnO and LZO thin films are obtained by low annealing temperature whereas the PbSe QDs-based absorber layer is deposited by layer-by-layer (LBL) technique in the presence of 1-ethyl-3-methylimidazolium iodide (EMII) which is acting as a ligand exchange material. Results show that 2 wt% Li-doping on one hand can maximumly increase the conduction band minimum, and transmittance, whereas on the other hand decreases the oxygen defects densities as well as the roughness of the thin film as compared to other ETLs. Subsequently, PbSe CQDSCs with 2 wt% Li-doped ZnO ETL display the highest power conversion efficiency (PCE) of 10.80% as compared to 10.12% PCE of ZnO-based PbSe CQDSCs (7.5% higher). Similarly, 2 wt% LZO-based PbSe CQDSCs devices show long-term stability of about 40 days. Furthermore, Li-doping in ZnO offers a viable approach for low-cost, high-performance CQDSCs.